2018
DOI: 10.1111/jai.13729
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of four fish species from the Yellow River, China

Abstract: Length‐weight relationships (LWRs) were estimated for four fish species [Schizopygopsis anteroventris Wu & Tsao, 1989, Schizothorax lissolabiatus Tsao, 1964, Triplophysa markehenensis (Zhu & Wu, 1981) and Triplophysa siluroides (Herzenstein, 1888)] from the Yellow River. Samples were collected seasonally from August 2016 to October 2017, using various fishing gears [set nets (mesh: 1.5 cm × 2.0 cm), hook, drift gill nets (mesh: 1.0 cm × 2.0 cm × 3.0 cm) and electro fishing]. Four new maximum standard length we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…The b value of 2.875 for Ptychobarbus kaznakovi was lower than the value of 2.918 previously reported for the Jinsha River (Lin et al, 2015) and 2.970 for the Zengqu River (Zhu et al, 2015). The b value of 3.090 for S. anteroventris in the present study exhibited a difference from previous values of 2.974 reported by Zhu et al (2017) and 2.540 reported by Pan et al (2018). For Cobitidae fishes (Table 2), the value of 2.847 for the b parameter of T. stolickai population was different from the value of 2.79 reported for the Ili River (Sui et al, 2015) and the value of 3.10 reported by Zhang et al (2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The b value of 2.875 for Ptychobarbus kaznakovi was lower than the value of 2.918 previously reported for the Jinsha River (Lin et al, 2015) and 2.970 for the Zengqu River (Zhu et al, 2015). The b value of 3.090 for S. anteroventris in the present study exhibited a difference from previous values of 2.974 reported by Zhu et al (2017) and 2.540 reported by Pan et al (2018). For Cobitidae fishes (Table 2), the value of 2.847 for the b parameter of T. stolickai population was different from the value of 2.79 reported for the Ili River (Sui et al, 2015) and the value of 3.10 reported by Zhang et al (2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Te allometric coefcient b exhibited variation across the species, ranging from a minimum of 3.073 for L. annandalei to a maximum of 3.335 for L. berdmorei. Te coefcient (b) values have proven to be a crucial parameter in the analysis of length-weight relationships (LWRs), serving as a signifcant indicator for predicting the overall growth status of species [32][33][34][35]. Te spectrum of b values was within the typical limit of our existing experiments and supports fndings similar to those of Pan et al [33] and Hossain [35].…”
Section: Discussionsupporting
confidence: 85%
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, ), the fish species were divided into two groups: (a) two species with b values within the Bayesian's confidence intervals ( S. lantsangensis and S. yunnanensis ); (b) a fish species of P. yunnanensis , estimated b value (2.68) was low in contrast to high b value (2.83–3.21) as per Bayesian approach (Froese & Pauly, ). LWR parameters may be influenced by a variety of factors such as diet, habitat, health, maturity status, preservation techniques, season and sex (Pan et al, ; Zhang et al, ; Zhu, Wang, Huang, & Yang, ); however, these factors were not considered in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Length‐weight relationships (LWRs) provide important data for fisheries research (Pan et al, ; Xiong et al, ; Xiong, Zhu, Xie, & Pan, ; Zhu & Yang, ; Zhu, Yang, Liu, & Li, ). The ichthyofauna of southwestern China is extremely diverse (Kang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation